DETERMINATION OF DIELECTRIC PROPERTY AND IONIC CONDUCTIVITY OF CdS/SO3H-P(S-DVB)] - Eriawan Rismana; Hadi Nur; Salasiah Endud (Jurnal Sains Materi Indonesia, 2012)
DETERMINATION OF DIELECTRIC PROPERTY AND IONIC CONDUCTIVITY OF CdS/SO3H-P(S-DVB)] nano composites with different CdS contents were successfully synthesized by ion exchange and precipitation processes at SO3H-P(S-DVB) matrix. The characterized, dielectric property and ionic conductivity of the nano composites were also examined. The polymermatrix and the chemical interaction between CdS nano particleswith polymer were analyzed using Fourier Transform Infrared (FT-IR) spectroscopy. The CdS nano particles was confirmed from Diffuse Reflectance Ultraviolet - Visible (DR UV-Vis), X-Ray Diffractometer (XRD) and Atomic Absorption Spectroscopy (AAS) analysis results. Scanning Electron Microscope (SEM) techniques were used to observe the particle size of the nano composites,while amorphology of the nano composites was also investigated using Transmission Electron Microscope (TEM) techniques. The SEM and TEM studies showed that the CdS nano particles are attached on the surface of polymer matrix. Dielectric property and ionic conductivity of the nano composites have been studied using an Impedance Analyzer, respectively. Present study shows that the influence of CdS nano particles loading levels on the dielectric property and ionic conductivity of the nano composites. The dielectric constant and ionic conductivity of the CdS/SO3H-P(S-DVB) nano composites decreased with increasing content of CdS nano particles as effect replacing of proton by CdS nano particles, respectively.